Hola Fresh / Aiyub Gams...[et al.] - Gams, Aiyub; Yusuf, Yurieka Audrey; Wahab, Nabila; Guman, Erne (Faculty of Business Management, 2013)
Hola Fresh is a mini cafe that located in 1 Borneo Hyper mall that allows the entire people get the real fresh juice that can give them satisfaction and feel the real feeling of fresh. Besides, we also provide waffle that very famous and become favourite to many people nowadays. Hola Fresh product is suitable for all types of ages either children or oldest. The juice that we sell is not just fresh but also give benefits to our customer, we produce the juice from fresh fruit that contains natural benefit that good for our health. Hola Fresh is able to serve the entire people in one quick convenient visit. While there are many "mini cafe" like Hola Fresh, Hola Fresh will excel due to its attention to detail regarding customer service. Through unheralded customer attention, Hola Fresh will slowly but surely gain market share as it services the all people, creating long-term relationships. Lastly, Hola Fresh location that just near with front door of the One Borneo Hyper mall will attract people to come. People in One Borneo have decided to come to Hola Fresh when they want to drink something fresh after tired shopping. They also can sit and for a while and have a conversation with their friend while enjoying the juice and waffle we serve. Hola Fresh will take this opportunity to provide the finest and highest quality of services to all customers, despite their age or gender.